Granular Cell tumor of the male breast - Baidya, R; Sigdel, B; Baidya, NL; Chakraborti, S (Journal of Pathology of Nepal, 2011)
A granular cell tumor is an unusual benign soft tissue neoplasm, occurring in the tongue, oral cavity or subcutaneous tissue and rarely occurs in the breast. We report a case of 44 years old male, who presented with a swelling in the right breast since 7 years measuring 6 x 4 cm. Fine needle aspiration cytology was suggestive of low grade carcinoma and on histopathologic examination, it was diagnosed as granular cell tumour, with S-100 immunopositivity. Keywords: Granular cell tumour; Male breast; S-100 DOI: http://dx.doi.org/10.3126/jpn.v1i2.5414 JPN 2011; 1(2): 161-163